Ba, Ra, Th, and U in marine mollusc shells and the potential of Ra-226/Ba dating of Holocene marine carbonate shells - Staubwasser, M; Henderson, G; Berkman, P; Hall, B (2004)
The geochemistry of Ba, Ra, Th, and U and the potential of using 226Ra/Ba ratios as an alternative dating method are explored in modern and Holocene marine mollusc shells. Five modern shells of the Antarctic scallop Adamussium colbecki collected from the present day beach and six radiocarbon dated specimens from Holocene beach terraces of the Ross Sea region (Antarctic) between 700 and 6100 calibrated yr BP old have been analysed by mass spectrometry. In clean shells 226Ra concentrations and 226Ra/Ba ratios show a clear decrease with increasing age, suggesting the possibility of 226Ra dating. Limiting factors for such dating are Ba and 226Ra present in surface contaminants, and ingrowth of 226Ra from U present within the shell. Surface contamination is difficult to clean off entirely, but moderate levels of residual contamination can be corrected using 232Th. Sub-samples from the same shell with different proportions of contamination form a mixing line in a 226Ra/Ba-232Th/Ba graph, and the 226Ra/Ba of the pure shell can be derived from the intercept on the 226Ra/Ba axis. Contaminant corrected 226Ra/Ba ratios of late-Holocene 14C-dated samples fall close to that expected from simple 226Ra excess decay from seawater 226Ra/Ba values. 226Ra ingrowth from U incorporated into the shell during the lifetime of the mollusc can be corrected for. However, the unknown timing of post mortem U uptake into the shell makes a correction for 226Ra ingrowth from secondary U difficult to achieve. In the A. colbecki shells, 226Ra ingrowth from such secondary U becomes significant only when ages exceed ∼2500 yr. In younger shells, 226Ra/Ba ratios corrected for surface contamination provide chronological information. If evidence for a constant oceanic relationship between 226Ra and Ba in the ocean can be confirmed for that time scale, the 226Ra/Ba chronometer may enable the reconstruction of variability in sea surface 14C reservoir ages from mollusc shells and allow its use as a paleoceanographic tracer. © 2004 Elsevier Ltd.